2013
DOI: 10.1186/1471-244x-13-302
|View full text |Cite
|
Sign up to set email alerts
|

Brain responses to body image stimuli but not food are altered in women with bulimia nervosa

Abstract: BackgroundResearch into the neural correlates of bulimia nervosa (BN) psychopathology remains limited.MethodsIn this functional magnetic resonance imaging study, 21 BN patients and 23 healthy controls (HCs) completed two paradigms: 1) processing of visual food stimuli and 2) comparing their own appearance with that of slim women. Participants also rated food craving and anxiety levels.ResultsBrain activation patterns in response to food cues did not differ between women with and without BN. However, when evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 53 publications
(94 reference statements)
0
30
0
2
Order By: Relevance
“…As in the current study, when the raw scores on the SAAS of the participants are compared, other studies have found [29,30] that ED patients obtained a higher score than control community groups. Although, to our knowledge, no research has analysed the role of gender and age in the specific fear of judgment based on appearance (SAA) in adult or adolescent samples, the gender and age differences across adolescents found in this research converged with a large body of research indicating that in general terms body and overall appearance concerns, social fears and particularly negative evaluation fears, and social anxiety are more salient from mid-adolescence onwards and across female participants [26,27,32,34,37,47,62,69].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…As in the current study, when the raw scores on the SAAS of the participants are compared, other studies have found [29,30] that ED patients obtained a higher score than control community groups. Although, to our knowledge, no research has analysed the role of gender and age in the specific fear of judgment based on appearance (SAA) in adult or adolescent samples, the gender and age differences across adolescents found in this research converged with a large body of research indicating that in general terms body and overall appearance concerns, social fears and particularly negative evaluation fears, and social anxiety are more salient from mid-adolescence onwards and across female participants [26,27,32,34,37,47,62,69].…”
Section: Discussionmentioning
confidence: 85%
“…Employing a female adult sample of 60 outpatients with EDs, Claes et al [10] supported the one-factor model of the SAAS and found that its score was significantly positive in relation to mistrust of others, social detachment, emotional lability and desire to become thinner. Evidence that ED patients obtained higher SAAS scores than matched healthy controls exists as well [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 The relevance of the sensorimotor and occipital regions to distorted body image has been emphasized in several previous studies. [9][10][11]14 For instance, reduced occipitotemporal responses during presentations of underweight or overweight human bodies were observed in patients with bulimia nervosa; 9 the lateral occipital activation was sensitive to stimuli of body size distortions in healthy people, whereas such a modulation was not observed in those with bulimia nervosa. 10 At rest, patients with bulimia nervosa showed abnormal iFC within the somatosensory network and between the paracentral lobule and 2 occipital regions.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesized that patients with bulimia nervosa would show abnormal topological properties in functional brain networks and that the functional disturbances would be apparent in the cortical and subcortical regions involved in reward and emotional processing, sensorimotor and visual perception, and interoception, based on potential relevance of these neural functions to bulimia nervosa. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] We also examined the behavioural/symptom correlates of these network properties.…”
Section: Functional Brain Network In Bulimia Nervosamentioning
confidence: 99%